Kajian Hubungan Panjang Bobot Ikan Belanak (Mugilidae) Di Perairan Sei Ladi Kota Tanjungpinang - Jamaludin, Jamaludin; Susiana, Susiana (Akuatiklestari, 2021)
Mugilidae is a dominant species of mullet in several Indonesian waters and its larvae are often found in coastal waters near river estuaries. This study aims to determine the relationship between the length and weight of female and male fish in Sei Ladi waters, Bugis Village, Tanjungpinang City. The research method was carried out through field surveys and primary data collection which was carried out by taking mullet fish samples, the data obtained were in the form of total length and weight of mullet. The results of research on growth of length and weight in mullet fish in Sei Ladi waters have a value of b = 0.0032 in male mullet, which means that it has a negative allometric growth pattern because it is smaller than 3 (b<3), and in female fish the value of b is obtained. = 0.0621 which indicates a negative allometric growth pattern because the b value is less than 3 (b<3).